2016
DOI: 10.3332/ecancer.2016.699
|View full text |Cite
|
Sign up to set email alerts
|

Replacing 5-fluorouracil by capecitabine in localised squamous cell carcinoma of the anal canal: systematic review and meta-analysis

Abstract: BackgroundThe standard treatment for localised squamous cell carcinoma of the anal canal (SCCAC) is chemoradiotherapy (CRT) with infusional 5-fluorouracil (5-FU) and mitomycin. Because 5-FU and capecitabine have offered similar efficacy in many phase-III trials of solid tumours, studies have tested capecitabine in this setting of SCCAC. However, these studies are small and have reported variable results. Therefore, a systematic review and meta-analysis was performed.MethodsMedline, Scopus and Embase were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
8
1
1
Order By: Relevance
“…The standard treatment for localized anal cancer is based on infusional 5-fluorouracil (5-FU) or capecitabine (7), mitomycin (MMC) or cisplatin, concomitant with external radiation. This provides excellent results with overall local control rates greater than 80% (2,8).…”
Section: Original Articlementioning
confidence: 99%
“…The standard treatment for localized anal cancer is based on infusional 5-fluorouracil (5-FU) or capecitabine (7), mitomycin (MMC) or cisplatin, concomitant with external radiation. This provides excellent results with overall local control rates greater than 80% (2,8).…”
Section: Original Articlementioning
confidence: 99%
“…NCCN, ESMO-ESSO-ESTRO, French Intergroup and relevant UK intensity-modulated radiation therapy (IMRT) guidelines support Capecitabine as an alternative option to 5-FU in radical CRT (18)(19)(20)(21). There is however a paucity of evidence for the tolerability and toxicity of Capecitabine when used in a doublet with MMC within this context (22,23). Notably, there is no relevant phase III data and the largest of the small number of relevant existing reports are retrospective, with significant heterogeneity in treatment parameters both within and across studies (24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of efficacy and manageable toxicity of the doublet MMC-C derived from retrospective studies (similar activity, but better tolerability of MMC-C versus MMC-5FU concomitant to IMRT, with lower hematologic toxicity and fewer treatment interruptions) and from phase II trials, with CR and locoregional control ranged from 77% to 89.1% and 79% to 94%, respectively, and high treatment completion rates despite the appearance of radiation dermatitis as the main toxicity (ranged from 23% to 63%). 32 40 The data regarding the combination of C with CDDP or oxaliplatin are more limited. 41 43 The main studies including C are reported in Table 5 .…”
Section: Discussionmentioning
confidence: 99%